Comparison of Business Revenue In Implementing Conventional and Digital Marketing On The Food Franchise Business (Case Study at Sego Njamoer Outlet) - Nona Rafifah Ri’at; Sri Tjondro Winarno; Ika Sari Tondang (International Journal of Economics, Business and Innovation Research, 2023)
This research aims to describe the application of digital marketing, analyze the income of Sego Njamoer franchise outlets, and analyze comparisons of purchase transactions at Sego Njamoer franchise outlets when carrying out conventional and digital marketing. The method of determining the sample by purposive sampling. Primary data collection by way of interviews assisted by using a questionnaire. The results of this study are: The Sego Njamoer franchise outlet uses social media marketing to advertise, and e-commerce as a place to make purchase transactions by customers. The income of the Sego Njamoer franchise outlet at Superindo Arif Rahman Hakim is IDR 40,608,887,- with an average income of IDR 4,794,369,-/month.T-test results from comparisons of purchase transactions, it can be concluded that digital marketing has been implemented can affect the income of Sego Njamoer franchise outlets.